Positive and psycho-pathological aspects between shame and shamelessness - Saya, Anna; Di Ciaccia, Gregorio; Niolu, Cinzia; Siracusano, Alberto; Melis, Marianna (Frontiers in Psychology, 2022)
Interpersonal relationships represent an essential aspect of mental well-being and social functioning. If all the symptoms contain a relational meaning, shame represents the relational affect par excellence both in terms of its origin and its purpose. This paper aims to highlight the role of shame as an affect inherent in the rhythmic nature of the encounter with the other, as well as the pathological elements of this aspect in both its conscious and unconscious dimensions. There is a heterogeneous quantitative and qualitative declination of shame, or of the defenses against this affect, among the various pathologies. We consider the fundamental needs of belonging and acceptance and the parallel abandonment anguish from various psychoanalytic and philosophical theoretical perspectives and then analyze the link between their dissatisfaction and the origin of shame. We also touch on the different interpretaions of shame based on eastern and western cultural norms. These hypotheses are closely intertwined with the beliefs of classical psychopathology. The role of the body in the encounter with the other and in the experience of shame is also examined. In particular, we study the role of this affect in schizophrenia, depression, eating disorders, and personality disorders.